Deuterated water and the formation of the satellites of Uranus - Michael E. Brown; Matthew Belyakov; Swaroop Chandra; M. Ryleigh Davis; Merritt McDowell; Ashma Pandya; Kevin T. Trinh; Samantha K. Trumbo (Proceedings of the National Academy of Sciences, 2026)
The satellites of Uranus orbit in a low-eccentricity, equatorial plane that is tilted by 98 ° relative to the solar system—a geometry that mirrors Uranus’s extreme axial tilt. Although a giant impact could have tipped Uranus, how the satellites came to share this orientation remains uncertain. Proposed formation pathways include primordial accretion followed by reorientation, formation from debris generated by the tilting impact, and reaccretion from a massive ring produced by the tidal disruption of passing bodies from the outer solar system. Current observations do not discriminate among these scenarios. Using the James Webb Space Telescope, we measured the deuterium-to-hydrogen (D/H) ratio in the water ice of the five regular satellites of Uranus. We find an average D/H ratio of 2.1 ± 0.2 × 10 − 4 , nearly five times higher than that of Uranus and comparable to values measured in comets. This enrichment is inconsistent with any formation scenario in which substantial Uranian material was incorporated into the satellites, thereby excluding models that require significant mixing in an impact-derived vapor disk. The observed D/H ratios are instead compatible with models in which the satellites accreted from material that remained largely separate from Uranus, such as debris from a disrupted preexisting satellite system or from a tidally captured outer solar system body. The innermost regular satellite, Miranda, exhibits a marginally elevated D/H ratio (2.8 σ above the average of the outer satellites), potentially indicating a distinct formation history or source of water and offering an important clue for distinguishing among competing models.